2019
DOI: 10.32615/ps.2019.008
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to photoinhibition within lichen species is higher in melanised thalli

Abstract: Some lichenized ascomycetes synthesize melanic pigments when exposed to ultraviolet light and high solar radiation. Here, we used chlorophyll fluorescence in order to test the effect of melanisation on the ability of the lichens Cetraria islandica, Lobaria pulmonaria, Peltigera aphthosa, P. membranacea, Pseudocyphellaria gilva, and Sticta sublimbata to tolerate highlight stress. For each species, melanised and pale thalli were selected from relatively exposed and shaded individuals of the same population. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
(37 reference statements)
2
14
0
Order By: Relevance
“…Earlier work (e.g. McEvoy et al 2007;Mafole et al 2019a) showed that photobionts in melanized lichens are more resistant to photoinhibition than those in pale ones, apparently due to fungal pigment synthesis. However, an inherent problem with these studies is that the melanized thalli were likely to have experienced stronger exposure to light than pale thalli.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier work (e.g. McEvoy et al 2007;Mafole et al 2019a) showed that photobionts in melanized lichens are more resistant to photoinhibition than those in pale ones, apparently due to fungal pigment synthesis. However, an inherent problem with these studies is that the melanized thalli were likely to have experienced stronger exposure to light than pale thalli.…”
Section: Discussionmentioning
confidence: 99%
“…2), consistent with the results of Mafole et al . (2019 a ). Protection was related to the absolute difference in reflectance between the pale and melanized thalli (compare Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, exposure to high or medium light levels of visible radiation for long periods in the dry state may result in accumulated severe damage (Gauslaa & Solhaug 1996; Gauslaa et al 2012; Mafole et al . 2019 b ).…”
Section: Avoidance By Light Screeningmentioning
confidence: 99%